2017
DOI: 10.1103/physrevb.95.014421
|View full text |Cite
|
Sign up to set email alerts
|

Goos-Hänchen shift of a spin-wave beam transmitted through anisotropic interface between two ferromagnets

Abstract: The main object of investigation in magnonics, spin waves (SWs) are promising information carriers. Presently the most commonly studied are plane wave-like SWs and SWs propagating in confined structures, such as waveguides. Here we consider a Gaussian SW beam obliquely incident on an ultra-narrow interface between two identical ferromagnetic materials. We use an analytical model and micromagnetic simulations for an in-depth analysis of the influence of the interface properties, in particular the magnetic aniso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Fabrication of magnonic waveguides. The Co-Fe waveguides were fabricated by FEBID employing the precursor HCo 3 Fe(CO) 12 . The precursors were injected in the SEM through a capillary with an inner diameter of 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Fabrication of magnonic waveguides. The Co-Fe waveguides were fabricated by FEBID employing the precursor HCo 3 Fe(CO) 12 . The precursors were injected in the SEM through a capillary with an inner diameter of 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the GH effect occurs when spin waves are scattered at the interface [36][37][38][39] , describing the shift between the reflected (or transmitted) point and the incident point. In the previous works, the sign of GH shifts can be positive or negative, depending on the reflection (or transmission) coefficients.…”
Section: A P Configurationmentioning
confidence: 99%
“…It's worth noting that spin waves are thermally excited by the spin Seebeck effect (SSE) in the experiments of magnon valves 20 and magnon junctions 21 , thus the coherence of spin waves is ignored. In fact, the coherence is important for spin-wave transmission because it can lead to plentiful physical phenomena, such as refraction [28][29][30][31][32][33][34] , skin effect 35 , Goos-Hänchen (GH) shift [36][37][38][39] , tunneling 40 , resonant tunneling 41,42 and resonant transmission [43][44][45][46] . Therefore, the systematic researches on the transmission of coherent spin waves in P and AP magnetic configurations are necessary, however few studies have reported on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the aim is to achieve maximum flexibility concerning manipulation such as steering of SWs with the ability to reduce the required footprint of a device while maintaining high-frequency operation [1]. So-called SW nano-optics [9] require the generation and manipulation of SW beams in the microwave frequency range and enable the realization of devices like SW fibers [10,11] or the exploitation of refraction and reflection effects [12][13][14]. Within the last few years, various approaches to generate SW beams were proposed and investigated.…”
Section: Excitation and Tailoring Of Diffractive Spin-wave Beams Inmentioning
confidence: 99%